2012
DOI: 10.1186/1741-7007-10-26
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes convert network excitation to tonic inhibition of neurons

Abstract: BackgroundGlutamate and γ-aminobutyric acid (GABA) transporters play important roles in balancing excitatory and inhibitory signals in the brain. Increasing evidence suggest that they may act concertedly to regulate extracellular levels of the neurotransmitters.ResultsHere we present evidence that glutamate uptake-induced release of GABA from astrocytes has a direct impact on the excitability of pyramidal neurons in the hippocampus. We demonstrate that GABA, synthesized from the polyamine putrescine, is releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
158
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(167 citation statements)
references
References 86 publications
6
158
2
1
Order By: Relevance
“…These authors found that transient receptor potential A1 channels (TRPA1) Under certain conditions, GATs can reverse their function to release GABA in the extracellular space. In two separate studies, Heja et al [79,80] found that astrocytes convert excitation to tonic inhibition of neurons in hippocampal slices and in in vivo experiments. In the presence of reduced Mg 2þ to increase network activity, they show that glutamate uptake is coupled to the reversal of GAT2/GAT3 that induces a GABA tonic current.…”
Section: Astrocytes Activated By Non-gabaergic Signals Modulate Gabaementioning
confidence: 99%
“…These authors found that transient receptor potential A1 channels (TRPA1) Under certain conditions, GATs can reverse their function to release GABA in the extracellular space. In two separate studies, Heja et al [79,80] found that astrocytes convert excitation to tonic inhibition of neurons in hippocampal slices and in in vivo experiments. In the presence of reduced Mg 2þ to increase network activity, they show that glutamate uptake is coupled to the reversal of GAT2/GAT3 that induces a GABA tonic current.…”
Section: Astrocytes Activated By Non-gabaergic Signals Modulate Gabaementioning
confidence: 99%
“…Furthermore, the average immunofluorescence density showed that the synthesis and secretion of GnRH neurons were suppressed in the immune hypothalamus. However, it is unclear by what mechanism thymulin upregulates GnRH in the immune hypothalamus: whether it involves plastic rearrangements of glial-GnRH neurons adhesiveness or the production of growth factors acting via receptors with tyrosine kinase activity remains to be determined (Mullier et al 2010, Heja et al 2012). …”
Section: Figurementioning
confidence: 99%
“…The latter decrease is reversed by a GABA uptake inhibitor, guvacine, which raises ambient GABA. GABA release by astrocytes also increases the gamma oscillation power in hippocampal area CA1 in vivo (9). Intriguingly, in hippocampal slices of animals lacking δ subunitcontaining GABA A receptors (which mediate tonic conductance in many local cell types including interneurons) the average frequency of cholinergically induced gamma oscillations is increased, whereas the oscillation power tends to drop (10).…”
mentioning
confidence: 99%